Analysis of sensitivity of the bonds: Duration and modified duration - Gomero Gonzales, Nicko Alberto (2018)
Objective: To determine the degree of sensitivity of a financial asset as it is of utmost importance for those who take risks for investing in the capital markets. Arriving to quantify the Maturation (M) and the Modified Maturity (DM) for these types of financial assets will allow investors to measure how the prices of the bonds change when the Rate of Return changes, therefore these indicators will give clear signals about the volatility of these assets and with it, investors will be able to take advantageous positions in these markets. Method: In order to model these cases, basic information about the profile of national bonds was used, specifically the information about their coupon rate, the expiration period and the rate of return. Results: The results obtained clearly demonstrate how the bonds become sensitized, which is a priority element to be taken into account when investing with hedged risks. Conclusions: The variation of the rate of return of a bond influences the Maturation and Modified Maturity as it also influences this asset price.